(3GdMGhj aj Yde GdJOGhjs - (3fLe GdOjf eMehO Hf UGFf GdOjf EdjGS GdTjQGRis; (3eMehO Hf UGFf GdOjf GdjGS GdTjQGRj, fLe GdOjf,J (B730 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdeGLO GdSHhM , NGdb GdLf hGdEfS, hQH GdedGFcI hGdQhM dCf TQa cd Yde hMSH ehVhYg hehVhY Yde GdWH HOf GdEfSGf hef GdHOjgjGJ Gf gPG GdehVhY ai YGde Gdchf s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hjfJgi eG ajgG CKfGA GdcdGe aj GdGOhjI GdeaQOI GdeSJYedI hBNQ GdehLhO efgG hdcd OQLI ef gPg GdCQHYI KdGKI eQGJH(B: (3YdjG hSadi hhSWi , eYfGg Chd OQLI hBNQgG hhSWgG s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B80 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs